2011
DOI: 10.1017/s0007114511001176
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry anthocyanin and its association with postprandial inflammation and insulin

Abstract: The present study investigates the effect of strawberry antioxidants in beverage form on meal-induced postprandial inflammatory and insulin responses in human subjects. Overweight adults (n 24) consumed a high-carbohydrate, moderate-fat meal (HCFM) accompanied by either a strawberry or a placebo beverage in a cross-over design. Postprandial changes in plasma anthocyanins, their metabolites, insulin, glucose and inflammatory markers were assessed for 6 h. The postprandial concentrations of pelargonidin sulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
203
8
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(240 citation statements)
references
References 41 publications
(58 reference statements)
22
203
8
7
Order By: Relevance
“…It is unclear why our results differ from the significant reductions in postprandial insulin (27,28), as well as triglycerides and oxidized LDL (26), found in the 2 previous postprandial strawberry studies. Dairy proteins and the timing of meal intake may diminish the effects of polyphenols (56,57); however, significant benefits have been achieved with the use of a milkbased beverage consumed with a test meal (26,28).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is unclear why our results differ from the significant reductions in postprandial insulin (27,28), as well as triglycerides and oxidized LDL (26), found in the 2 previous postprandial strawberry studies. Dairy proteins and the timing of meal intake may diminish the effects of polyphenols (56,57); however, significant benefits have been achieved with the use of a milkbased beverage consumed with a test meal (26,28).…”
Section: Discussioncontrasting
confidence: 99%
“…Although the amount of strawberries required to optimize effects on clinical outcomes is unknown, our 40-g dose of freeze-dried powder was equivalent to w3 cups of fresh strawberries [13 g freeze-dried powder is equivalent to 1 cup fresh (C Christian California Strawberry Commission, personal communication, 2014)] and provided a substantial amount of polyphenols (Supplemental Table 2). A similar amount of total anthocyanins was provided in the postprandial study by Park et al (28), although the freeze-dried strawberry powder used by BurtonFreeman and colleagues (26,27) had a higher oxygen radical absorbance capacity value and a higher concentration of select polyphenolic compounds, including quercetin and pelargonidin-3-glucoside. These differences may account, in part, for the discrepancies between our results and those of Burton-Freeman et al (26).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We, along with others, have shown that consumption of a meal that is high in readily available carbohydrates and fat results in an increase in markers of oxidative stress and inflammation postprandially [8][9][10][11][12][13]. These changes are accentuated in obesity, diabetes and individuals with the MetS [14].…”
mentioning
confidence: 83%
“…Fruits and vegetables, particularly those with higher polyphenolic content, have favorable effects on human health due to their ability to modulate oxidative and inflammatory stress in peripheral tissues [12,13,15]. These effects have also been associated with improvements in insulin sensitivity [16] and postprandial insulin responses [9]. Grape seeds are a concentrated source of polyphenols and have received considerable attention for their antioxidant capacity and biological effects after chronic consumption [17][18][19][20].…”
mentioning
confidence: 99%